Respuesta :

Answer:

f(1) = -3

f(-4) = -11

f(6) = 0

Find where your inputs make sense.
For the first problem it asks to find the input of f(1), the second constraint would be correct because 1 is less than for 4 and negative 2. Then you would plug in your values.
So -3(1)=-3
The second one fits the constraints of the first so plug it in for 2x-3. You would get 2(-4)-3, which equals -11
For the last one find what value corresponds to the input value of 6 and then plug it in.
6/6 -1 =0
Hope this helped you understand.
ACCESS MORE